Pemberdayaan Masyarakat melalui Pariwisata Olahraga di Ubud, Bali: Sebuah Studi Empiris - I Putu Surya Anggana; Dewa Agus Yuda Ariawan; Antonietta Gizela Dethan; Luh Ade Syah Sugiarni (Indonesian Journal of Sport and Tourism, 2026)
This research explores how sport tourism contributes to the empowerment of local communities in Ubud, Bali, emphasizing its economic, social, and cultural dimensions. Employing a mixed-method approach, the study engaged 120 local participants and 25 key informants drawn from government bodies, village authorities, and event organizers. The findings reveal that events such as trail running, yoga retreats, and cycling festivals have improved small business revenues by approximately 16–22%, expanded temporary job opportunities by more than 150%, and created new platforms for local cultural performances. Despite these benefits, several constraints persist, including limited managerial skills, unequal benefit distribution, and insufficient access to financing. The study concludes that sport tourism holds substantial potential to empower Ubud’s community when it is supported by participatory planning, enabling policy frameworks, and inclusive microfinance mechanisms.